Carprofen and buprenorphine prevent hyperalgesia in a model of inflammatory pain in cats - Taylor, P. M.; Steagall, P. V. M.; Dixon, M. J.; Ferreira, T. H.; Luna, Stélio Pacca Loureiro [UNESP] (Elsevier B.V., 2007)
A model of nociceptive threshold determination was developed for evaluation of NSAID analgesia in cats. In a crossover study, eight cats received carprofen (4 mg/kg), buprenorphine (0.01 mg/kg) or saline (0.3 ml) subcutaneously before intradermal kaolin injection on the antebrachium to induce mild inflammation. Pressure thresholds were measured at the injected site using blunt-ended pins advanced by manual inflation of a bladder within a bracelet. Bladder pressure was recorded as threshold (PT) at the behavioural end point. Baseline PT were recorded before kaolin injection (time 0). PT was measured at 2-10 h intervals for 52 h. PT below the lower 95% confidence interval (CI) of baseline values indicated hyperalgesia. After saline, hyperalgesia was detected from 2-6 h, 22-26 h, and at 30 and 36 h. After carprofen, PT remained within the 95% CI. After buprenorphine, PT remained within the 95% CI except at 2 h. Carprofen and to some extent buprenorphine, prevented inflammatory hyperalgesia. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: cat; analgesia; pain; pressure nociceptive threshold testing; opioid; NSAID